Who Gains the Benefits of On-Task Versus Off-Task Self-Assessment? Higher or Lower Proficiency? - Herlinawati Herlinawati; M. Fadhly Farhy Abbas (Lectura : Jurnal Pendidikan, 2017)
This study was attempted to investigate the effects of two different types of selfassessment:on-task versus off-task on EFL Indonesian students’ writing performanceacross different proficiency level. The on-task self-assessment asked the students toself-evaluate their performance immediately after they completed their English writingtasks. The off-task self-assessment asked the students to evaluate their overallperformance in a general and somewhat in de-contextualized way. The total number offorty-eight (48) students participated in this study and randomly assigned into twoexperimental groups. The data was gained from the post-test (essay writing test). Theresults indicated that the low proficiency students in on-task self-assessment groupposed a significant effect and they could self-assess their writing performance moreaccurately than they had in an off-task format. In conclusion, on-task self-assessment issuggested to be implemented for lower achievers to consolidate their writingperformance. However, further research is suggested to conduct to know the students’experiences in applying on-task and off-task self-assessment as an effective writingstrategy.